2010
DOI: 10.1007/s00468-010-0467-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of stable carbon isotopes, plant water potential and growth: an approach to asses water use efficiency and growth strategies of dry land agroforestry species

Abstract: The relationships between annual wood stable carbon isotope composition (d 13 C), dry season midday plant water potential, and annual growth rate were investigated to asses the ability of agroforestry species to adapt to climate changes. 6-8 stem disks from four co-occurring species (Acacia senegal, A. seyal, A. tortilis and Balanites aegyptiaca) were collected for radial growth measurements using tree-ring analysis spanning 1930-2003. Annual d 13 C was measured on three tree disks per species for the period 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 35 publications
2
39
0
1
Order By: Relevance
“…Most of the stem discs obtained from an enclosed ranch, where human disturbance is negligible, could be crossdated (Gebrekirstos et al 2008). Radial growth variations of crossdated trees studied at the Abernosa woodlands suggested that Acacia tortilis and Balanites aegyptiaca are more tolerant to drought, but less Trees vigorous under wetter conditions than Acacia senegal and Acacia seyal (Gebrekirstos et al 2008), supporting findings by Gebrekirstos et al (2006Gebrekirstos et al ( , 2010.…”
Section: Lowlandssupporting
confidence: 56%
“…Most of the stem discs obtained from an enclosed ranch, where human disturbance is negligible, could be crossdated (Gebrekirstos et al 2008). Radial growth variations of crossdated trees studied at the Abernosa woodlands suggested that Acacia tortilis and Balanites aegyptiaca are more tolerant to drought, but less Trees vigorous under wetter conditions than Acacia senegal and Acacia seyal (Gebrekirstos et al 2008), supporting findings by Gebrekirstos et al (2006Gebrekirstos et al ( , 2010.…”
Section: Lowlandssupporting
confidence: 56%
“…Beside these exceptions (Bao9, Bao20), all sampled trees showed similar mean values for annual growth. Mean δ 13 C values varied about 1.8 per mille between trees, which is relatively little compared to 3 or up to 5 per mille stated for trees in other studies (loader et al 2003;skomarkova et al 2006;GeBrekirstos et al 2011). An increase in mean δ 13 C values was accompanied by decreasing variances most likely due to plant-physiological processes.…”
Section: Discussionmentioning
confidence: 92%
“…The resulting treering width time series were synchronized with TSAPWin (Time Series Analysis and Presentation for Dendrochronology and Related Applications;version 4.67c © 2002version 4.67c © -2011. The program allows visual and statistical crossdating by matching patterns of thin and wide rings (Fritts 1976) and illustrates discrepancies between the series. Areas of uncertain dating were reviewed in WinDENDRO TM and corrected if necessary.…”
Section: Crossdating and Chronology Buildingmentioning
confidence: 99%
“…Information on d 13 C fractions can be used to estimate changes in water use efficiency or long-term changes in internal CO 2 concentration (C i ). For ten tropical tree species long-term trends in stable isotope levels have now been obtained (Hietz et al 2005;Gebrekirstos et al 2009;Nock et al 2010;Brienen et al 2010b;Gebrekirstos et al 2010). A decrease in d 13 C over time was reported, which led to an increase in intrinsic water use efficiency (iWUE) for six species (Hietz et al 2005;Nock et al 2010;Brienen et al 2010b).…”
Section: Fluctuations In Growing Conditions and Physiological Responsmentioning
confidence: 97%